The girl who lost a leopard - Farook, Nizrana (Atlanta : Peachtree, 2023)
Twelve-year-old Selvi loves the animals that live on the mountains behind her home, particularly the beautiful golden leopard, Lokka, and she is determined to protect him from the hunter Jansz who both threatens not only Lokka, but Selvi's family as well.
5-8.
English.
Keywords: Animal rescue -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Hunters -- Juvenile fiction; Leopard -- Juvenile fiction; Animal rescue -- Fiction; Human-animal relationships -- Fiction; Hunters -- Fiction; Leopard -- Fiction; Animal rescue -- Fiction; Human-animal relationships -- Fiction; Hunters -- Fiction; Leopard -- Fiction; Sri Lanka -- Juvenile fiction; Sri Lanka -- Fiction; Sri Lanka -- Fiction